Analysis of Oil Composition of Native Almonds from Turkey - ÇELIK*, FERIT; FIKRET BALTA†, M.; JAVIDIPOUR‡, I.; DOGAN, ADNAN (Asian Journal of Chemistry, 2009)
Native almond genotypes contained 43.5-62.4 % oil, 5.61-16.48 %palmitic acid, 0.32-0.69 % palmitoleic acid, 1.23-3.89 % stearic acid,68.99-81.71 % oleic acid, 7.70-21.65 % linoleic acid, 0.08-0.21 %linolenic acid and 0.22-0.91 % myristic acid. In addition, they had 78.74-92.97 % unsaturated fatty acid content, 7.03-21.28 % saturated fattyacid content and 3.7-13.2 unsaturated fatty acid/saturated fatty acid ratio.